Review: Implementasi Holap Untuk Optimasi Query Sistem Basis Data Terdistribusi Dengan Pendekatan Algoritma Genetik - Syaifudin, Rahmad; Selo, Selo; Hartanto, Rudy (Universitas Diponegoro, 2014)
Distributed Database is one of database that is under control of the Database Management System (DBMS) was focused on storage devices are separated from one and another. Optimization data query on distributed database system not be separated from data processing methods that used. Then for fast query optimization this database need some required methods that can optimize it. Hybrid online analytical processing (HOLAP) or often to call Hybrid-OLAP is one of technology for optimization query on distributed database. Genetic Algorithm is one of algorithm for heuristic searching was based on the mechanisms of biological evolution. Process of genetic algorithm is combining a selection process, using a crossover operator and mutation to get the best solution. From the reviews about implementation HOLAP with Genetic Algorithm approach was expected being used as a basis research on HOLAP implementation for query optimization on distributed database with genetic algorithm approach. Keywords : Query Optimization; Distributed database; HOLAP; OLAP; Genetetic algorithm.